Applying Geographical Information System (GIS) process in Search And Rescue (SAR) operation of hiking incidents / Norsyazlin Mohd Rosli, Nur Shaffiqa Muhammad Soffian and Amelia Ahmad - Mohd Rosli, Norsyazlin; Muhammad Soffian, Nur Shaffiqa; Ahmad, Amelia (2022)
Hiking is now one of the most popular outdoor adventure activities among Malaysian community. For more than 10 years, hiking incidents have occurred frequently among hikers, whether in mountain hiking areas, hills or in public recreational parks with relatively low hills. Incidents during hiking can occur even if various complete preparations have been made prior to the hike. Preparation in terms of database about the hiking area's condition is not available such as hiking area background, tree, forest, and slope. With the availability of database, it will support the Search and Rescue (SAR) operation that includes safety of SAR team; coordination of resources and monitoring of operation, and post-operation analysis, planning and documentation. The implementation of IR4.0, the benefits of using technologies such as GIS that serve to form a more systematic database are seen to be able to deal with incidents during hiking. The aim of the paper is to formulate hiking incidents prevention database systems with GIS application. The objective of the current paper is to clarify the issues related to SAR operation, and environmental variables that will be used to generate spatial and attributes data. The paper applies a deductive research methodology, which includes content analysis which focuses on the process of GIS formation. The development of a database using GIS is seen to be able to help in managing the hiking area and the hiker themselves to be better prepared in the event of an incident during hiking.